2008
DOI: 10.1093/carcin/bgn052
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-delivered CIAPIN1 small interfering RNA inhibits HCC growth in vitro and in vivo

Abstract: Hepatocellular carcinoma (HCC) is an aggressive cancer with a poor prognosis. The specific cellular gene alterations responsible for hepatocarcinogenesis are not well known. Cytokine-induced antiapoptotic molecule (CIAPIN1), a recently reported antiapoptotic molecule which plays an essential role in mouse definitive hematopoiesis, is considered a downstream effecter of the receptor tyrosine kinase–Ras signaling pathway. However, the exact function of this gene in tumors is not clear. In this study, we reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…3 Long-term survival of patients with HCC is uncommon due to the frequent presence of reoccurrence, metastasis, or the development of new primaries. 4 Curative treatment such as hepatic resection and liver transplantation can be utilized when HCC is diagnosed at an early stage. 5,6 Unfortunately, when diagnosed the vast majority of liver cancers are inoperable, [7][8][9] and thus the patients have to receive chemotherapy, which has limited success due to the fact that HCC is intrinsically resistant to standard chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…3 Long-term survival of patients with HCC is uncommon due to the frequent presence of reoccurrence, metastasis, or the development of new primaries. 4 Curative treatment such as hepatic resection and liver transplantation can be utilized when HCC is diagnosed at an early stage. 5,6 Unfortunately, when diagnosed the vast majority of liver cancers are inoperable, [7][8][9] and thus the patients have to receive chemotherapy, which has limited success due to the fact that HCC is intrinsically resistant to standard chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, li et al observed that, in p53 wild-type Hepg2 and sMMc-7721 cells, apoptosis induced by AdsicIApIn1 (adenovirus-delivered cIApIn1 small interfering rnA) partially resulted from accumulation of p53 protein, indicating cIApIn1 might inhibit the expression or accumulation of p53 (11). For loVo cells is known to express wild-type p53 (6), we investigated the role of p53 in the cIApIn1-related MDr in present study.…”
Section: Ciapin1 Conferred Mdr In Lovo Cells In a P53-independentmentioning
confidence: 86%
“…therefore, cIApIn1 conferring MDr in cancer cells via regulating the expression of mutant p53 is not comprehensive. More recently, li et al found that down-regulation of cIApIn1 by adenovirusdelivered small interfering rnA could result in enhanced expression of p53 protein in Hepg2 and sMMc-7721 cells that contained wild-type p53 gene (11). It seems reasonable that cIApIn1 mediated MDr in wild-type p53 loVo cells via inhibiting expression of p53 (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies on the relationship www.intechopen.com between CIAPIN1 and tumor formation showed that CIAPIN1 expression was increased significantly in HCC, gastric cancer and other malignant tumor tissues (Ida et al, 2007;. Li (Li et al, 2008) used adenovirus-mediated RNAi to knock out CIAPIN1 in HCC cells and found that CIAPIN1 gene expression in HCC cells was down-regulated, where cells were prevented from entering phase S and cell proliferation was inhibited. Eight weeks after injection of adenovirus/siRNA between transplanted tumor tissues, the tumor size was only one-sixth of the control group, and pathological sections showed apoptotic cells in tumor tissues.…”
Section: Cytokine-induced Apoptosis-inhibiting Moleculementioning
confidence: 99%